Company Size as a Moderator of Factors Influencing Earnings Quality - Henny Wirianata; Rusi Rusi; Metio Alberto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to obtain empirical evidence of the influence of profitability, profit growth, liquidity, leverage, Investment Opportunity Set, and firm size on earnings quality. This study also uses firm size as a moderating variable. The study population includes non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2021–2024. The research data sample was taken using purposive random sampling. The data in the study were processed and analyzed using panel data regression analysis without moderation and with moderation using eviews. The results of the panel data regression analysis using the Fixed Effect Model (FEM) indicating that all independent variables simultaneously have a significant effect on earnings quality. Leverage, Investment Opportunity Set (IOS), and firm size indicate no significant effect on earnings quality. Moderation regression analysis shows that firm size moderates the effect of profitability and leverage on earnings quality, indicating that larger firms have better oversight and governance mechanisms in managing earnings and debt. Conversely, firm size does not moderate the effect of profit growth, liquidity, and Investment Opportunity Set (IOS) on earnings quality. This finding indicates that high earnings do not necessarily reflect quality earnings. Companies are advised to strengthen their internal control systems and increase the transparency of financial reporting to minimize earnings management practices. Investors are expected to focus not only on profit levels and profitability, but also consider the quality of earnings and the company's overall financial structure when making investment decisions.